HYDRAULIC BATTERY AS ELEMENT OF THE HYDRAULIC-MECHANICAL SYSTEM AND ITS DYNAMIC MODEL - A.T. RYBAK (Advanced Engineering Research, 2007)
It is given to information on methods dynamic calculation hydraulic systems, is offered conclusion to dynamic model of the hydraulic battery with pneumatic spring and its brought three-dementional acerbity.